Rohingya Refugees and Human Trafficking in Indonesia: A PRISMA-Based Review of Legal and Policy Gaps - Gunawan, Alief; Setiyono, Budi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
The humanitarian crisis involving Rohingya refugees has become a complex issue affecting the Southeast Asian region, particularly Indonesia, which has received several waves of refugee arrivals. The Rohingya, a Muslim ethnic minority from Myanmar, have long endured systematic discrimination, culminating in a mass exodus of over 700,000 individuals in 2017 following military operations by the Myanmar government. The presence of Rohingya refugees in Indonesia presents not only humanitarian concerns but also increases the risk of exploitation by human trafficking networks (TPPO). This study aims to analyse Indonesia’s policy response to the Rohingya refugee crisis, with a specific focus on efforts to prevent human trafficking. A Systematic Literature Review (SLR) method was employed, reviewing 21 selected academic sources. The analysis evaluates the effectiveness of Indonesian government policies, the legal and institutional challenges in refugee protection, and the role of cooperation with international organisations such as UNHCR and IOM. The findings reveal that while Indonesia has provided temporary humanitarian assistance, its current policy framework remains insufficient to mitigate the refugees' vulnerability to trafficking. The study underscores the need for enhanced collaboration among the state, civil society, and international actors, as well as for a clearer legal framework grounded in human rights principles. Strengthening social protection mechanisms is essential to ensure that Rohingya refugees are safeguarded from exploitation and treated with dignity.